Weed Vegetation Analysis and Response to Sunflower Extracts in the Uplands - Winda Purnama Sari; Fitri Ekawati; Jamsari Jamsari (Department of Crop Science, Faculty of Agriculture, Andalas University, 2024)
Weeds are plants whose presence is unwanted by humans because of competition with cultivated plants for nutrients, sunlight, and growing space, producing allelochemicals that interfere with plant growth, reduce production and product quality, and increase farming costs. The continuous use of synthetic herbicides has adverse effects on the environment and health, so it is necessary to seek a weed control mechanism that is more efficient and environmentally friendly. One is utilizing secondary metabolites, namely sunflower plant allelochemicals, that can control weeds. This study aims to determine the response of weeds to the application of extracts of sunflower plant parts as bioherbicides. This research was conducted in three stages: raw material preparation, extraction, and application. The results obtained 17 weed species in the experimental field of Nagari Selayo Tanang Bukit Sileh from 7 families (Asteraceae, Poaceae, Lythraceae, Polygonaceae, Brassicaceae, Caryophyllaceae, and Mazaceae) and two weed classes (broadleaf weeds and grasses). The bioherbicide efficacy of sunflower extract (Helianthus annus L.) has not caused symptoms of toxicity in weeds.